Pengaruh Pemberian VCO Terhadap Penyembuhan Luka Perineum Pada Ibu Nifas di PMB Sri Suparti - Sri Suparti; Sri Kustiyati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: In Indonesia perineal lacerations are experienced by 75% of women giving birth vaginally due to spontaneous tearing. This can cause bleeding to not be stopped properly or infection to occur. To prevent infection of perineal wounds, perineal wound care can be done using virgin coconut oil (VCO) which has properties as an antiseptic, anti-infection and can reduce pain and provide comfort. Objective: To determine the effect of VCO administration on perineal wound healing in normal postpartum women at PMB Sri Suparti Karanganyar. Research method: The type of research used is quasi-experimental research. The research design used the post test only with control group design method with 30 samples, 15 were given VCO and 15 were not given VCO by processing the data using Mann Whitney. The results of the study: The results of the data analysis test with Mann Whitney obtained a value of p = 0.001, with a significant level of p <0.05 which means that there is an effect of VCO administration on perineal wound healing in normal postpartum mothers. Conclusion: There is an effect of VCO administration on perineal wound healing in normal postpartum women at PMB Sri Suparti Karanganyar.